CFD analysis of thermal fields for ice abrasive water jet. (15th April 2022) - Jerman, Marko; Orbanić, Henri; Valentinčič, Joško
Highlights: Validated CFD model was used to determine the temperatures of the water jet The water jet cools down when passing the water nozzle Main heating occurs in the region adjacent to the jet occupied by the carrier gas Ice particles with d ≥ 0.5 mm should be used if water jet is not cooled Ice particles with d ≥ 0.3 mm can be used if water jet is cooled Abstract: Ice abrasive water jet (IAWJ) technology uses ice particles instead of the mineral abrasives used in abrasive water jet (AWJ) technology. Since the thermal conditions are extremely important for the survival of the ice particles and their mechanical properties, the temperatures of the water jet and the adjacent air are analysed for different pressures and temperatures of the water upstream of the water nozzle and different nozzle orifice diameters. The temperature fields are calculated with a fully validated Computational Fluid Dynamic (CFD) model. The results show that the temperature of the jet core does not change significantly, but the adjacent air heats up considerably due to viscous heating; both are influenced by the water temperature and pressure upstream of the water nozzle. A low water temperature upstream of the water nozzle could significantly reduce the expected temperature of the ice particles exiting the cutting head. However, the use of a cold carrier gas such as nitrogen with a temperature of -196°C should not have a significant effect on the temperature of the ice particles inside the cutting head. It is recommended to optimise the geometry of the cutting head to reduce the travel time of the ice inside. If water cooling is not used, the ice particles should have a diameter of more than 0.5 mm. However, if cooling is used, particles as small as 0.3 mm in diameter can be used. The observed temperature conditions play a key role in the further development of IAWJ technology. Abstract : Image, graphical abstract